Evaluation of Maize Genotypes for Agro-morphological and Yield Traits under Mid-hill Conditions of Nepal - Khanal, Dinesh (Journal of Agriculture and Forestry University, 2025)
The present study was conducted to evaluate the extent of agro-morphological variability, heritability, and genetic advance among nine maize genotypes, with the aim of identifying traits useful for yield improvement. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. The plot size was 3m×2.5m with the spacing of 60cm×25cm and the experiment was carried out from June 2019 to October 2019. Data were recorded on key phenological, morphological, and yield-related traits, including plant height, ear height, days to 50% tasseling and silking, anthesis–silking interval, ear and plant aspects, yield components, and grain yield. Data were analyzed through R-Studio. Analysis of variance revealed significant differences among genotypes for most of the traits studied, indicating the presence of sufficient genetic variability. Grain yield varied widely, ranging from 4.12 to 9.65 t ha⁻¹, with a mean yield of 6.69 t ha⁻¹. For most of the traits, the value of genotypic coefficient of variation (GCV) was close to the phenotypic coefficient of variation (PCV), suggesting that the observed variation was largely governed by genetic factors with minimal environmental influence. High heritability (≥0.80) was observed for days to 50% tasseling, days to 50% silking, ear height, and number of ears per plot. Among these traits, ear height exhibited high heritability coupled with substantial genetic advance, indicating the predominance of additive gene action. The high heritability and genetic advance observed in several traits are particularly important because the evaluated genotypes mainly consisted of hybrids and released varieties, which are generally expected to show reduced variability. The presence of high heritable variation in these materials suggests that further genetic improvement through selection is feasible. Therefore, ear height emerged as a reliable selection criterion for improving grain yield and overall performance in maize breeding programs.